Competitive advantages in Malaysian specialty chemical business / Abdullah Abdul Ghani, Tengku Nazri Tengku Muda and Zamri Mohamad - Abdul Ghani, Abdullah; Tengku Muda, Tengku Nazri; Mohamad, Zamri (2007)
The research is focusing on competitive advantage in specialty chemical business in Malaysia. Case study on MACES Sdn Bhd (MACES) on how the company identify the element and subsequently will contribute in achieving its company objective to become a market leader in provision of specialty chemical supply and associated services. The industry External Environmental Factors (EFE) as well as Internal Environmental Factors (IFE) which are the driving forces of the business were identified and analyzed. The study also included analysis on Competitors SWOT by industry and identifies the strategic positioning of the specialty chemical business players. These tools would assist MACES to identify its position in the industry.